THE EFFECT OF MOTIVATION, TEACHING AND LEARNING PROCESS FACILITIES, AND THE DISCIPLINE ON THE TEACHERS’ PERFORMANCE IN THE STATE SENIOR HIGH SCHOOL (SMAN) 1 JULOK, EAST ACEH REGENCY - Hanafiah Hanafiah; Hartutik Hartutik; Sukirno Sukirno (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2020)
This study aims to find out how the influence of each of the motivational variables, teaching and learning facilities, and discipline on the performance of teachers in SMA N 1 Julok, East Aceh Regency. This research uses quantitative methods using statistical data analysis. Data collection techniques in this study used a questionnaireaire. The results showed: (1) Because tcount (X1) = 4.648 while ttable = 1.684 then tcount> ttable, the hypothesis was accepted and the Sign value was 0,000 <0.05 and a regression equation model Y = 11.388 + 0.594 X1 + 0.128 was obtained. So, there is a significant influence between motivation on teacher performance in Julok State 1 High School, East Aceh Regency. (2). Because the value of tcount (X2) = 0.250 while ttable = 1.684 then tcount <ttable, the hypothesis is accepted and the Sign value is 0.804> 0.05 and a regression equation model Y = 11.338 + 0.032X2 + 0.127 is obtained. Therefore, there is no significant influence between the teaching and learning process facilities on the performance of teachers in the State High School 1 Julok, East Aceh Regency. (3). Because the value of tcount (X3) = 0.417 while ttable = 1.684 then tcount <ttable, the hypothesis is accepted and the Sign value is 0.679> 0.05 and a regression equation model Y = 11.388 + 0.64X3 + 0.154 is obtained. Thus, there is no significant influence between discipline on the performance of teachers in the State High School 1 Julok, East Aceh Regency. (4). Because the value of Fthitung = 19.530 while Ftable = 2.84 then Fcount> Ftable, the hypothesis is accepted and the value of Sig. 0,000 <0.05 and the regression equation model Y = 11.389 + 0.594 X1 + 0.032 X2 + 0.064 X3 + 4.496 is obtained. Therefore, it can be concluded that there is a significant influence between motivation, teaching and learning process facilities, and discipline on teacher performance in the Julok State High School 1 East Aceh Regency. Keywords: Motivation, Teaching and Learning Process Facilities, Discipline, Teacher Work, SMAN 1 Julok, East Aceh Regency.